Macroporous Acrylamide Phantoms Improve Prediction of In Vivo Performance of In Situ Forming Implants - Hernandez, Christopher (J Control Release, 2016)
In situ forming implants (ISFIs) have shown promise as a sustained, local drug delivery system for therapeutics in a variety of applications. However, development of ISFIs has been hindered by poor correlation between in vitro study results and in vivo performance. In contrast to oral dosage forms, there is currently no clear consensus on a standard for in vitro drug dissolution studies for parenteral formulations. Recent studies have suggested that the disparity between in vivo and in vitro behavior of phase-inverting ISFIs may be, in part, due to differences in injection site stiffness. Accordingly, this study aimed to create acrylamide-based hydrogel phantoms of various porosities and stiffness, which we hypothesized would better predict in vivo performance. Implant microstructure and shape were found to be dependent on the stiffness of the phantoms, while drug release was found to be dependent on both phantom porosity and stiffness. Specifically, SEM analysis revealed that implant porosity and interconnectivity decreased with increasing phantom stiffness and better mimicked the microstructure seen in vivo. Burst release of drug increased from 31% to 43% when in standard acrylamide phantoms vs macroporous phantoms (10 kPa), improving the correlation to the burst release seen in vivo. Implants in 30 kPa macroporous phantoms had the best correlation with in vivo burst release, significantly improving (p < 0.05) the burst release relative to in vivo from 64%, using a standard PBS dissolution method, to 92%. These findings confirm that implant behavior is affected by injection site stiffness. Importantly, with appropriate optimization and validation, hydrogel phantoms such as the one investigated here could be used to improve the in vitro-in vivo correlation of in situ forming implant formulations and potentially augment their advancement to clinical use.